Personal papers in the universities of five continents. Issue 1 (January 2020) - Ocejo, Yolanda Cagigas; Hernández, Inés Irurita; Ochoa, Esther Eslava
Abstract : In Spain, the number of universities holding " archivos personales " is growing. This article analyses, on a global scale, the management of personal papers in 110 universities selected from across all continents and within diverse archival cultures. The starting point is an examination of terms similar to " archivo personal " in English and French. The main sources used are the database of the Multilingual Archival Terminology project (led by Dr. Luciana Duranti), the official websites of each of the 110 selected universities, their own publications on their " fondos personales " and the results of surveys carried out among responsible for the archives. The analysis of all the data obtained provides, on a comparative basis, answers to questions such as: why do universities keep " fondos personales "? How do they acquire them? How do they describe them? What kind of services are provided to make these records available for research?